2017
DOI: 10.1162/artl_a_00231
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evolution of Robot Morphologies: A Proof of Concept

Abstract: Evolutionary robotics using real hardware has been almost exclusively restricted to evolving robot controllers, but the technology for evolvable morphologies is advancing quickly. We discuss a proof-of-concept study to demonstrate real robots that can reproduce. Following a general system plan, we implement a robotic habitat that contains all system components in the simplest possible form. We create an initial population of two robots and run a complete life cycle, resulting in a new robot, parented by the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 39 publications
0
63
0
Order By: Relevance
“…The Triangle of Life concept (discussed below) has been demonstrated with a simplified setup by Jelisavcic et al (2017), where physical robots were 3D-printed and handassembled, also using prefabricated organ, such as servo motors and Raspberry Pis. The ARE project will take this further through the automated Robot Fabricator, allowing larger numbers of individuals and a complete evolutionary system to be fabricated.…”
Section: Related Workmentioning
confidence: 99%
“…The Triangle of Life concept (discussed below) has been demonstrated with a simplified setup by Jelisavcic et al (2017), where physical robots were 3D-printed and handassembled, also using prefabricated organ, such as servo motors and Raspberry Pis. The ARE project will take this further through the automated Robot Fabricator, allowing larger numbers of individuals and a complete evolutionary system to be fabricated.…”
Section: Related Workmentioning
confidence: 99%
“…This means that the evolutionary operator's mutation and crossover are applied to the genotypes (to the code) and not to the phenotypes (to the robotic organisms). The first stage in the ToL is the creation of a new robotic organism in a so-called Production Center [19]. This stage starts with a new piece of genetic code that is created by mutating or recombining existing pieces of code (of the robot parents) and ends with the delivery of a new robot.…”
Section: System Architecture: the Triangle Of Lifementioning
confidence: 99%
“…We design the modular robots using a subset of the components: brick components, a core component, and active hinges [29], which is based on Robogen [4]. The brick components are cubic with four slots on their sides available for other modules to attach to.…”
Section: Robot Morphologiesmentioning
confidence: 99%
“…"go 2 Related work Evolutionary robotics aims to design adaptive robots automatically that can evolve to accomplish a specific task while adapting to environmental changes [2]. A number of studies have demonstrated the feasibility of evolutionary methods for generating robotic control and/or morphology [29].…”
Section: Introductionmentioning
confidence: 99%